Copper Sulfides: Small‐Sized CuS Nanoparticles/N, S Co‐Doped rGO Composites as the Anode Materials for High‐Performance Lithium‐Ion Batteries (Adv. Mater. Interfaces 6/2019). Issue 6 (22nd March 2019) - Ding, Xueda; Lei, Song; Du, Chengfeng; Xie, Zailai; Li, Jianrong; Huang, Xiaoying
Abstract : Small‐sized CuS nanoparticles/N, S co‐doped rGO composites are synthesized by using metal‐containing ionic liquids as the multifunctional precursors, which are investigated as promising host electrode materials for high‐performance lithium‐ion batteries. More details can be found in article number 1900038 by Xueda Ding, Chengfeng Du, Jianrong Li, and co‐workers.